M*A*S*H. Season eleven [videorecording (DVD)] - Metcalfe, Burt; Alda, Alan, 1936-; Swit, Loretta; Farrell, Mike; Morgan, Harry, 1915-2011; Gelbart, Larry (Twentieth Century Fox Home Entertainment, 2005)
Explores the day-to-day lives of the people who live and work at the Mobile Army Surgical Hospital (MASH) stationed three miles from the front during the Korean War.